A case of acute renal failure requiring emergency hemodialysis due to hypothermia-associated rhabdomyolysis - Vural, Abdussamed; Ekiz, Mehmet; Günaydın, Mücahit (Journal of Surgery and Medicine, 2020)
Hypothermia is described as a decrease in body temperature below 35 °C. Although the body reacts neuroendocrinally, behaviourally, and cardiovascularly against sudden changes in temperature, uncontrolled hypothermia can lead to severe complications such as rhabdomyolysis, acute renal failure, coma, coagulopathy, malignant cardiac arrhythmia, and cardiac collapse. Herein, we aimed to emphasize hypothermia, its serious complications such as rhabdomyolysis and related acute kidney injury in a 60-year-old male patient exposed to environmental cold.